2021
DOI: 10.1080/2000656x.2021.1873793
|View full text |Cite
|
Sign up to set email alerts
|

The proximal ulnar perforator flap (PUPF) for hand digital reconstruction: an anatomical study

Abstract: Degloving injuries of the fingers represent a reconstructive challenge. Even if poorly described in literature, the proximal ulnar perforator flap (PUPF), based on perforator of the anterior ulnar recurrent artery or directly on a perforator branch of the ulnar artery, meets the requested criteria for the ideal coverage. We performed a cadaveric study in order to clarify the anatomical basis and vascularization of the PUPF flap. Eight injected upper limb specimens were dissected for this study: perforators wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Despite being first described in 1984 by Lovie et al, 18 the PUPF is not well documented in the literature, unlike other flaps 19 , 20 ; however, it offers significant advantages. In 2014, Wei et al 12 published a study that confirmed the PUPF’s continuous and stable blood supply, as well as its advantages over the radial flap in terms of donor site care, scar placement, and skin graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being first described in 1984 by Lovie et al, 18 the PUPF is not well documented in the literature, unlike other flaps 19 , 20 ; however, it offers significant advantages. In 2014, Wei et al 12 published a study that confirmed the PUPF’s continuous and stable blood supply, as well as its advantages over the radial flap in terms of donor site care, scar placement, and skin graft loss.…”
Section: Discussionmentioning
confidence: 99%